The Dynamics of Fan Communication on a K-Drama Menfess Twitter Account: A Netnographic Study of Virtual Communities - Devy Putri Kussanti; Nur Iman El Hidayah; Dhefine Armelsa; Ita Suryani; Mareta Puri Rahastine (Jurnal Spektrum Komunikasi, 2026)
This study uses netnography to trace the activities of the K-Drama Menfess Twitter account as a means of communication and virtual discussion for Korean drama fans. This approach helps researchers understand the dynamics of social life in cyberspace through observation of online activities that occur naturally on the platform. The research focuses on analyzing the interactions, activities, and content or menfess posted by the account's followers, which reflect the forms of communication, expression, and engagement within the K-Drama fan community. The research method used in this study is a qualitative or naturalistic method that produces descriptive data in the form of written or spoken behavior and words from the subjects. Research data was collected through participatory observation and content analysis of tweets published by the K-Drama Menfess account during a certain period of time. The results of the study show that this account plays an important role in building a solid and interactive virtual community. The account not only serves as a space for sharing information and opinions about K-Drama, but also strengthens the sense of togetherness among community members. These findings emphasize the importance of social media as a dynamic virtual communication space that contributes to enriching the experiences and knowledge of its users.